A Two Stage Stochastic Semidefinite Relaxation for Wireless Ofdma Networks - Soto-Gomez, J (Elsevier B.V., 2011)
In this paper, we propose a two stage stochastic binary quadratic program for OFDMA wireless networks. The aim is to minimize the total power consumption of the network subject to user bit rates, sub-carrier and modulation constraints. We derive from the quadratic model a linear (LP) and a semidefinite programming (SDP) relaxation. Numerical results show tight and near optimal bounds for the SDP relaxation. © 2011 Elsevier B.V.